Crash risk in morbidly obese drivers before and after bariatric surgery: A population-based cohort study - Junaid Ahmad Bhatti (366799) (2015)
Morbid obesity is a major public health problem in high-income, developed and fast developing countries. The potential effects of morbid obesity on road crash risk have rarely been investigated. In this study, we evaluated road crash risks in morbidly obese drivers who underwent bariatric surgery. We conducted a self-matched cohort analysis of morbidly obese adult patients in Ontario (Canada) who underwent bariatric surgery between April 1, 2006 and March 31, 2011. We used a province-wide emergency department database to determine their involvement in a road crash as a driver. We compared crash incidence per 1,000 patient-years in the three-year interval before surgery to three years after surgery. The cohort included a total of 8,815 patients; most (81%) were women. About 4% (n=333) of them were involved in a crash during six years of follow-up. Of them, 175 had 182 crashes before surgery and 165 patients had 174 crashes after surgery. The road crash incidence was similar before and after surgery, i.e., 7 per 1,000 patient-years. This road crash incidence was three times higher than the population rate of 2 per 1,000 patient-years. Crash risks were similar before and after surgery among those who were diagnosed with an obstructive sleep apnea (Incidence rate ratio [IRR]= 0.95, 95% Confidence Interval [CI] = 0.73 - 1.23) and other patients (IRR = 0.96; 95% CI=0.69-1.37). Morbid obesity may be associated with increased crash risk. These findings favor crash risk assessment in morbidly obese drivers. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.16